VOCABULARY ERRORS, SPEAKING, AND SELF-CONFIDENCE STUDENTS AT SMP NEGERI 3 CIOMAS - Ridwan Nurmansah (Universitas Indraprasta PGRI, 2022)
This study aims to: 1) The process of using words, speaking and students' self-confidence in learning English. 2.) To determine the factors that cause students who know the low level of students in learning English speaking skills. 3.) To see how students deal with them. This research was conducted using a qualitative method (case study). This research was conducted at SMP Negeri 3 Ciomas Bogor. This research was conducted from October to completion. With a sample size of 10 students with low proficiency in English subjects. By using two research instruments, namely questionnaires and interviews and strengthened by triangulation. The results show that preparation is the strategy most used by students to reduce their English-speaking skills research.